Modern Research in the Field of Microencapsulation (Review) - Yu. A. Polkovnikova; N. A. Kovaleva (Разработка и регистрация лекарственных средств)
Introduction. Microencapsulation is one of the promising areas for obtaining new dosage forms. The peculiarity of microencapsulated forms is that the substance is protected from the effects of various environmental factors that can cause their destruction (acidity of gastric juice, the effect of food, joint intake of other drugs, diseases of the gastrointestinal tract, etc.). This method is used for various groups of drugs, such as antibiotics, nootropics, vitamins, probiotics, anticonvulsants, enzymes. Particular attention should be paid to antibacterial drugs, since the possibility of microencapsulation solves one of the most important problems in antibiotic therapy – the resistance of microorganisms.Text. The purpose of the review is to analyze modern research in the field of microencapsulation, to study trends and directions for the creation of microcapsules with high activity and bioavailability and with minimal side effects. The article provides brief information and main conclusions on the development of techniques and selection of conditions for microencapsulation of individual medicinal substances, on the study of polymers of various natures for use as carriers, on the methods of forming double shells of microcapsules, and also investigated the efficiency of microencapsulation of biologically active substances, such as antibacterial preparations, substances of plant and animal origin and preparations from various pharmacological groups. Variants of microencapsulation techniques for specific compounds that are suitable for substances similar in composition and action, as well as methods for creating microcapsules with double shells for compounds insoluble in water, are presented.Conclusion. The article shows the achievements and prospects of using microencapsulation of medicinal substances and their advantages over standard dosage forms. The active introduction of the developed methods into production will allow the creation of new dosage forms with known medicinal substances that have a prolonged effect, which will reduce the frequency of use of the drug, as well as retain their activity under the influence of negative factors of the internal environment of the body. Also, in the form of microcapsules, the substances are more active in comparison with non-encapsulated substances.